Evaluation of Increased Serum Aminotransferase Level in Asymptomatic Patient - Suharjo Brata Cahyono (The Indonesian Society for Digestive Endoscopy, 2011)
Liver test abnormalities are commonly found in ambulatory patients. The liver function tests are routinely included in chemistry panels. According to the American Gastroenterological Association (AGA), 1-4% of the asymptomatic population may have elevated serum liver chemistry. The majority of asymptomatic patients with liver test abnormalities have no evidence of liver disease. Unfortunately, abnormal Results for liver function are often not adequately investigated, missing an important chance of identifying treatable chronic liver disease. Potential causes of liver aminotransferase elevation are originated from hepatic causes (viral hepatitis, alcohol use, medication use, steatosis and non-alcoholic steatosis hepatitis, autoimmune hepatitis, hemochromatosis, Wilson’s disease, α-antitrypsin deficiency) and non hepatic causes. In the majority patients (92%) with chronically elevated aminotransferase tests, etiologies of the liver disease could be diagnosed through close clinical approach, which includes: history taking, physical examination, and blood tests. If elevation persists after an appropriate period of observation, further testing may include ultrasonography and other serum studies. In about 8% of patients with chronic abnormal alanine aminotransferase levels no cause is found. So, if liver test abnormalities cannot be explained by other findings, liver biopsy examination can help to exclude serious liver disease or disclose the nature and severity of liver disease. Keywords: elevated liver transaminase, asymptomatic patients, chronic liver disease